Self-regulation and motivation teacher in non-formal education: A systematic literature review - Yuniarini, Putu Dina; Agung, Anak Agung Gede; Ariawan, I Putu Wisna; Sulindawati, Ni Luh Gede Erni (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the relationship between self-regulation and teaching motivation for educators in non-formal education. Being an educator is a very noble profession, regardless of the burdens and responsibilities held. Teaching is about transferring knowledge to students and transforming knowledge for students. To form a supportive learning environment for students, educators must certainly have aspects of self-regulation and high motivation in the teaching process. These two aspects are important because they are interconnected and affect an educator's teaching and learning process; this is the main focus of this study. The study used the systematic literature review approach with the PRISMA model based on literature relevant to the study's focus. The literature study results provide an idea that self-regulation has an important relationship with increasing educator motivation. Educators with good self-regulation are more motivated in teaching, able to control emotions and pressure, and better able to form a comfortable learning environment. The study's results also found that efforts in developing self-regulation are very important because they are directly related to strengthening the quality of education. The results of this literature review can provide important insights into the aspects that affect educators in teaching, especially in non-formal educational institutions.